From Network Management System to Network Management Cloud——The Way to Intensive Network Management - Hong Li; Kai Qu; Wenhong Zhou; Siyuan Wu; Wenjun Shen (Dianxin kexue)
Intensive network management will become the focus in the future. Automation and intelligentization of network management are based on the integration of network management system. Several kinds of technical architectures were discussed to build intensive network management system. A revolutionary way was tried to be found to adjust to the features of network management. The way is to integrate all network management systems into a big cloud named NM-Cloud.